Synthesis and characterization of new aromatic polyesters containing biphenyl side groups - Honkhambe, Pandurang N.; Avadhani, C. V.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (Journal of Applied Polymer Science, 2007)
Aromatic polyesters containing biphenyl side groups were synthesized by phase-transfer catalyzed interfacial polycondensation of 1-(4-biphenylyl)-1,1-bis(4-hydroxyphenyl) ethane (BBHPE) with terephthaloyl chloride (TPC), isophthaloyl chloride (IPC), and a mixture of TPC/IPC (50: 50 mol ratio). Copolyesters were synthesized by utilizing different molar proportions of BBHPE and 4,4-isopropylidenediphenol (BPA) with IPC and TPC. The inherent viscosities of polyesters were in the range 0.44-1.26 dL/g. All the polyesters were soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, meta-cresol, pyridine, N,N-dimethylformamide, N,N-dimethylacetamide, and 1-methyl-2-pyrrolidmone. Tough, transparent, and flexible films could be cast from chloroform solutions of these polyesters. WAXD measurements indicated that all the polyesters and copolyesters were amorphous in nature. Glass transition temperature of polyesters were in the range 198-256 degrees C, while the initial degradation temperature of polyesters were in the range 444-481 degrees C. Copolyesters derived from BBHPE exhibited improved solubility and higher glass transition temperatures compared to the corresponding polyesters based on BPA. (c) 2007 Wiley Periodicals, Inc.
Keywords: Aromatic polyesters; biphenyl side groups

Synthesis of aromatic poly(amide-imide)s from novel diimide-diacid (DIDA) containing sulphone and bulky pendant groups by direct polycondensation with various diamines - Patil, Prashant S.; Pal, Ravindra R.; Salunkhe, Manikrao M.; Maldar, Noormahamad N.; Wadgaonkar, Prakash P. (European Polymer Journal, 2007)
A novel diimide-diacid (DIDA) monomer, 4-{4-[(4-methyl phenyl) sulphonyl]}-1,3-bis-trimellitoimido benzene containing sulphone and bulky pendant groups was successfully synthesized and used to synthesize a series of wholly aromatic poly(amide-imide)s (PAIs) by direct polycondensation method. The direct polycondensation of newly synthesized DIDA with different diamines was carried Out via Yamazaki's phosphorylation method using triphenyl phosphite and pyridine system. The resulting poly(amide-imide)s were obtained in quantitative yields with inherent viscosities 0.36-0.47 dl/g in DMAc at 30 +/- 0.1 degrees C. The poly(amide-imide)s were amorphous and were readily soluble in various solvents such as N-methyl-2-pyrrolidinone (NMP), NN-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF), dimethylsulfoxide (DMSO), and pyridine. Tough and flexible films were obtained by casting their DMAc solution. According to thermogravimetric analysis, the polymers were fairly stable up to temperature around 396 degrees C, and 10% weight losses in the temperature range of 476-511 degrees C that showed good thermal stabilities of these polymers. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: direct polycondensation; poly(amide-imide)s; sulphone and bulky pendant groups; thermally stable polymers

Synthesis, characterization and constitutional isomerism study of new aromatic polyamides containing pendant groups based on asymmetrically substituted meta-phenylene diamines - Pal, Ravindra R.; Patil, Prashant S.; Salunkhe, Manikrao M.; Maldar, Noormahamad N.; Wadgaonkar, Prakash P. (European Polymer Journal, 2009)
Four new aromatic polyamides containing pendant groups were synthesized by low temperature interfacial polycondensation of two asymmetrically substituted diamine monomers, namely, 4-[4-(1-methyl-1-phenylethyl) phenoxyl-1,3-diamino benzene and 4-[4-[4-methylphenyl) sulphonyl]phenoxy)-1,3-diamino benzene with two aromatic diacid chlorides, namely isophthaloyl chloride and tereplithaloyl chloride. Inherent viscosities of polyamides were in the range 0.64-0.72 dL/g indicating formation of medium molecular weight polymers. The weight average molecular weights and number average molecular weights, determined by gel permeation chromatography (polystyrene standard), were in the range 54,500-65,000 and 19,750-27,000, respectively. The constitutional isomerism of synthesized polyamides was investigated by (1)H and (13)C NMR spectroscopy, where as the constitutional order was calculated from (1)H NMR spectroscopy and was found to be in the range 0.35-0.37. Polyamides containing pendant groups were essentially amorphous and were soluble in polar aprotic solvents such as N, N-dimethyl acetamide, N-methyl-2-pyrrolidone, N, N-dimethyl formamide and dimethyl sulfoxide. Polyamides exhibited glass-transition temperature in the range 237-254 degrees C. The initial decomposition temperature, determined by TGA in nitrogen atmosphere, of polyamides was in the range 371-410 degrees C indicating their good thermal stability. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Asymmetrically substituted diamines; Constitutional isomerism; interfacial polycondensation; Pendant groups

Synthesis and characterization of new aromatic polyesters containing pendent naphthyl units - Honkhambe, Pandurang N.; Biyani, Mahesh V.; Bhairamadgi, Nagendra S.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (Journal of Applied Polymer Science, 2010)
Two bisphenols, viz., 4,4'-[1-(2-naphthaleny-1)ethylidene]bisphenol and 4,4'-[1-(2-naphthalenyl) ethylidene]bis-3-methylphenol were prepared by condensation of commercially available 2-acetonaphthanone with phenol and o-cresol, respectively. A series of new aromatic polyesters containing pendent naphthyl units was synthesized by phase-transfer-catalyzed interfacial polycondensation of these bisphenols with isophthaloyl chloride, terephthaloyl chloride, and a mixture of isophthaloyl chlorideiterephthaloyl chloride (50 : 50 mol %). Inherent viscosities of polyesters were in the range 0.83-1.76 dL g(-1), while number average molecular weights (M(n)) were in the range 61,000-235,000 g mol(-1). Polyesters were readily soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, m-cresol, pyridine, N,N-dimethylformamide, N,N-dimethylacetarnide, and 1-methyl-2-pyrrolidinone at room temperature. Tough, transparent, and flexible films were cast from a solution of polyesters in chloroform. X-Ray diffraction measurements displayed a broad halo at 20 congruent to 19 degrees indicating the amorphous nature of polyesters. Glass transition temperatures of polyesters were in the range 209-259 degrees C. The temperature at 10% weight loss (T(10)), determined by TGA in nitrogen atmosphere, of polyesters was in the range 435-500 degrees C indicating their good thermal stability. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 117: 2545-2552, 2010
Keywords: Aromatic polyesters; bisphenol; interfacial polycondensation; pendent naphthyl units

Synthesis and characterization of new aromatic polyesters containing cardo decahydronaphthalene groups - Honkhambe, Pandurang N.; Bhairamadgi, Nagendra S.; Biyani, Mahesh V.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (European Polymer Journal, 2010)
Three cardo bisphenols containing decahydronaphthalene group viz., 4,4'-(octahydro-2(1H)-naphthylidene)bisphenol, 4,4'-(octahydro-2(1H)-naphthylidene)bis-3-methylphenol and 4,4'-(octahydro-2(1H)-naphthylidene)bis-3,5-dimethylphenol were synthesized starting from commercially available 2-naphthol and were utilized for synthesis of new aromatic polyesters by phase transfer-catalyzed interfacial polycondensation with isophthaloyl chloride, terephthaloyl chloride and a mixture of isophthaloyl chloride and terephthaloyl chloride (50:50 mol %). Inherent viscosities and number average molecular weights (M(n)) of polyesters were in the range 0.35-0.84 dL/g and 13300-48,500 (Gel Permeation Chromatography, polystyrene standard), respectively. Polyesters were readily soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, meta-cresol, pyridine, N,N-dimethylformamide, N,N-dimethylacetamide, and 1-methy1-2-pyrrolidinone at room temperature and could be cast into tough, transparent and flexible films from their chloroform solutions. Wide-angle X-ray diffraction measurements revealed the amorphous nature of polyesters. The glass transition temperature of polyesters was in the range 207-287 degrees C. The temperature at 10% weight loss (T(10)), determined from thermogravimetric analysis of polyesters, was in the range 425-460 degrees C indicating their good thermal stability. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: bisphenol; Cardo; Decahydronaphthalene; polyester; Structure-property relationship

Poly(ether ether ketone)s and poly(ether ether ketone ketone)s containing cardo decahydronaphthalene groups: synthesis and characterization - Honkhambe, Pandurang N.; Pasale, Sharad K.; Bhairamadgi, Nagendra S.; Kumbhar, Kishor P.; Salunkhe, Manikrao M.; Wadgaonkar, Prakash P. (Journal of Applied Polymer Science, 2011)
New poly(ether ether ketone)s and poly (ether ether ketone ketone) s were synthesized by polycondensation of each of the three bisphenols, viz., 4,4'-(octahydro-2(1H)-naphthylidene) bisphenol, 4,4'-(octa-hydro-2(1H)-naphthylidene) bis-3-methylphenol, and 4,4'(octahydro-2(1H)-naphthylidene) bis-3,5-dimethylphenol with 4,4'-difluorobenzophenone and 1,3-bis(4-fluorobenzoyl) benzene in a mixture of N,N-dimethylacetamide and toluene [1 : 1 (v/v)] in the presence of anhydrous potassium carbonate. Inherent viscosities of poly(ether ether ketone) s and poly (ether ether ketone ketone) s were in the range 0.32-0.80 dL/g and number-average molecular weights were in the range 16,100-55,900 g/mol. Poly(ether ether ketone) s and poly(ether ether ketone ketone) s were soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, meta-cresol, pyridine, and 1-methyl-2-pyrrolidinone at room temperature and could be cast into tough, transparent, and flexible films from their chloroform solutions. Wide angle x-ray diffraction measurements revealed the amorphous nature of poly(ether ether ketone) s and poly (ether ether ketone ketone) s. The glass transition temperature poly(ether ether ketone) s and poly(ether ether ketone ketone) s were in the range 185-251 degrees C. The temperature at 10% weight loss, determined from thermogravimetric analysis, of poly(ether ether ketone) s and poly(ether ether ketone ketone) s in nitrogen atmosphere was in the range 462-493 degrees C indicating their good thermal stability. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 122: 1607-1613, 2011
Keywords: bisphenol; cardo decahydronaphthalene; poly(ether ether ketone ketone)s; poly(ether ether ketone)s; Polycondensation; Thermal properties

Synthesis, spectroscopy, and electrochemical investigation of new conjugated polymers containing thiophene and 1,3,4-thiadiazole in the main chain - Patil, Prashant S.; Haram, Nanda S.; Pal, Ravindra R.; Periasamy, N.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (Journal of Applied Polymer Science, 2012)
Novel photoluminescent donoracceptor poly(p-phenylenevinylene)-type conjugated polymers containing thiophene and 1,3,4-thiadiazole units in the main chain were synthesized from 2,5-bis(5-bromomethyl-2-thienyl)-1,3,4-thiadiazole and 1,3/1,4-benzenedialdehyde by WittigHorner reaction. The synthesized polymers were characterized by the use of thermal analysis and spectroscopic (infrared, UV-visible absorption, and photoluminescence) measurement. The resultant material exhibited bluish green, green, and orange fluorescence in their solution and thin film and solid forms, respectively. The redox property of the polymers has also been studied by cyclic voltammetry. The optical and electrochemical studies reveal that these novel polymers are new promising materials for the development of efficient polymer light-emitting diodes. (c) 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: conjugated polymers; photoluminescence; thiophene and thiadiazole-containing polymer

Synthesis and characterization of poly(ether ether ketone)s and poly(ether ether ketone ketone) s containing pendant biphenyl and naphthyl groups - Honkhambe, Pandurang N.; Dhamdhere, Neelam A.; Tawade, Bhausaheb V.; Salunkhe, Manikrao M.; Wadgaonkar, Prakash P. (High Performance Polymers, 2013)
New poly(ether ether ketone)s (PEEKs) and poly(ether ether ketone ketone)s (PEEKKs) containing pendant biphenyl and naphthyl groups were synthesized by nucleophilic substitution reaction of each of the four bisphenols viz., 1-(4- biphenylyl)- 1,1- bis(4- hydroxyphenyl) ethane, 1-(4- biphenylyl)- 1,1- bis(3- methyl, 4- hydroxyphenyl) ethane, 4,4'-[1-(2- naphthalenyl) ethylidene] bis-phenol and 4,4'-[1-(2- naphthalenyl) ethylidene] bis-3-methylphenol with 4,4'- difluorobenzophenone and 1,3- bis(4- fluorobenzoyl) benzene in a solvent mixture of N,N-dimethylacetamide and toluene in the presence of anhydrous potassium carbonate. Inherent viscosities and number-average molecular weights of polymers were in the range of 0.42-0.86 dl/g and 2.40-7.55 x 10(4), respectively. PEEKs and PEEKKs were amorphous in nature and were readily soluble in a wide range of organic solvents and could be cast into flexible and tough films from chloroform solution. Glass transition temperature of PEEKs and PEEKKs were in the range of 180 degrees C -200 degrees C. T-10 values of PEEKs and PEEKKs were in the range of 424 degrees C-512 degrees C in nitrogen atmosphere, indicating their good thermal stability.
Keywords: biphenyl; bisphenol; naphthyl; poly(ether ether ketone ketone)s; poly(ether ether ketone)s; Polycondensation; Thermal properties